2022
DOI: 10.1155/2022/2045619
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of the miRNA-mRNA Regulatory Network Reveals the Biomarker Genes in the Progression of Myocardial Ischemic Reperfusion

Abstract: Objective. Cardiac injury induced by myocardial ischemic reperfusion (MI/R) is still an intractable question in clinical, and it has been confirmed as a major reason for the development of cardiovascular disease. Bioinformatics analysis has been widely used for revealing the pathogenic mechanism of diseases. This study attempted to identify the biomarkers and reveal the regulation mechanism of MI/R injury via bioinformatics analysis. Methods. The GSE67308 and GSE74951 were obtained from the GEO database. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The analysis revealed that DEG was enriched in metabolic pathways, oxidative phosphorylation, extracellular matrix receptor interaction, Epstein-Barr virus infection, chemokine receptor pathway, phagosomes, proteasomes, etc. Li and Chen (2022) (27) carried out an enrichment analysis, and it suggested that normal genes were correlated with inflammatory response, immune response, PI3K/AKT, NF-κB, and TNF pathways. In addition, mmu-miR-92a-3p and mmu-miR-27b-3p were identified as central miRNA, and TNF, IL1B, and IFG1 were screened as critical nodes.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis revealed that DEG was enriched in metabolic pathways, oxidative phosphorylation, extracellular matrix receptor interaction, Epstein-Barr virus infection, chemokine receptor pathway, phagosomes, proteasomes, etc. Li and Chen (2022) (27) carried out an enrichment analysis, and it suggested that normal genes were correlated with inflammatory response, immune response, PI3K/AKT, NF-κB, and TNF pathways. In addition, mmu-miR-92a-3p and mmu-miR-27b-3p were identified as central miRNA, and TNF, IL1B, and IFG1 were screened as critical nodes.…”
Section: Discussionmentioning
confidence: 99%
“…Journal of Healthcare Engineering has retracted the article titled “Analysis of the miRNA-mRNA Regulatory Network Reveals the Biomarker Genes in the Progression of Myocardial Ischemic Reperfusion” [ 1 ] due to concerns that the peer review process has been compromised.…”
mentioning
confidence: 99%